2018
DOI: 10.2147/prbm.s184014
|View full text |Cite
|
Sign up to set email alerts
|

Mild and severe childhood depression: differences and implications for prevention programs in the school setting

Abstract: PurposeThe study had two goals as follows: 1) to identify the prevalence of children with mild and severe depression (MD and SD), exploring sex differences; and 2) to determine possible significant differences in adaptive and clinical variables between children with different levels of depression (absence of depression, MD, and SD).Materials and methodsWe used a sample of 420 participants aged 7–10 years (53.3% boys) enrolled in third and fourth grade of primary education, from schools in the Basque Country (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
4
5
0
1
Order By: Relevance
“…That is, teachers rarely detected students with depressive symptomatology or even detected “false positives”. These findings are similar to those found in other studies (Bernaras et al, 2015; Cicchetti et al, 2010; Kleftaras & Didaskalou, 2006; Sternberg et al, 2006), although they differ from the results found by Achenbach et al (1987), who found a moderate overlap between different informants. The results obtained in the present study confirm teachers’ low capacity to identify child depression, which emphasizes the importance of training teachers in matters related to mental health and particularly, in depressive symptomatology.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…That is, teachers rarely detected students with depressive symptomatology or even detected “false positives”. These findings are similar to those found in other studies (Bernaras et al, 2015; Cicchetti et al, 2010; Kleftaras & Didaskalou, 2006; Sternberg et al, 2006), although they differ from the results found by Achenbach et al (1987), who found a moderate overlap between different informants. The results obtained in the present study confirm teachers’ low capacity to identify child depression, which emphasizes the importance of training teachers in matters related to mental health and particularly, in depressive symptomatology.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, the results have shown that students with depressive symptomatology presented low academic performance scores (assessed through the perception of academic success that the teacher had of his/her student), thus confirming the posed hypothesis, in line with the conclusions obtained in other studies (Bernaras et al, 2013, 2015; Moyeda et al, 2009; Orgilés et al, 2014; Suhrcke & de Paz Nieves, 2011; Wu & Kuo, 2015). However, it also should be noted that teachers perceive a greater relationship between performance and depression than that indicated by the results when taking into account the students’ self-reports on their depressive symptomatology.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The possible impact that all these aspects can have on school performance in children has also been studied and, although the conclusions are not consistent, it is an aspect that should be considered in the long-term follow-up of these children [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%